Alocação de blocos de recursos em redes LTE utilizando estimativa de limitante de retardo através de cálculo de rede - Ferreira, Marcus Vinícius Gonzaga (2015)
In this work we propose an algorithm to allocate resource blocks for LTE (Long Term Evolution) communication systems that takes into account the maximum delay guarantee and MCS (Modulation and Coding Scheme) constraints on the downlink transmission. At first, we propose an allocation algorithm which tries to reduce user‘s delay using the information of the network real delay and the channel transmission quality. Next, we propose an allocation algorithm which considers the channel transmission quality and the delay target, which is estimated through Network Calculus using service curve and MFBAP (Multifractal Bounded Arrival Process) envelope process, in order to decide on the scheduling of available radio resources. Comparisons with other allocation algorithms are carried out through QoS (Quality of Service) parameters such as average delay, total throughput, loss rate, fairness and processing time, verifying the efficiency of the proposed algorithm.